Targeting Endothelial Dysfunction in Vascular Complications Associated with Diabetes - Arpeeta Sharma; Pascal N. Bernatchez; Judy B. de Haan (International Journal of Vascular Medicine)
Cardiovascular complications associated with diabetes remain a significant health issue in westernized societies. Overwhelming evidence from clinical and laboratory investigations have demonstrated that these cardiovascular complications are initiated by a dysfunctional vascular endothelium. Indeed, endothelial dysfunction is one of the key events that occur during diabetes, leading to the acceleration of cardiovascular mortality and morbidity. In a diabetic milieu, endothelial dysfunction occurs as a result of attenuated production of endothelial derived nitric oxide (EDNO) and augmented levels of reactive oxygen species (ROS). Thus, in this review, we discuss novel therapeutic targets that either upregulate EDNO production or increase antioxidant enzyme capacity in an effort to limit oxidative stress and restore endothelial function. In particular, endogenous signaling molecules that positively modulate EDNO synthesis and mimetics of endogenous antioxidant enzymes will be highlighted. Consequently, manipulation of these unique targets, either alone or in combination, may represent a novel strategy to confer vascular protection, with the ultimate goal of improved outcomes for diabetes-associated vascular complications.